Evaluation and selection of CMIP6 GCMs for long-term hydrological projections based on spatial performance assessment metrics across South Korea - Nguyen Thi Huong; Yong-Tak Kim; Hyun-Han Kwon (Journal of Water and Climate Change, 2023)
The selection of an appropriate subset of Global Climate Models (GCMs) from the Coupled Model Intercomparison Project 6 (CMIP6) for long-term hydrological simulation at the basin scale is a necessity. This study selected high-performing GCMs among 32 available CMIP6 GCMs on the basis of reproducing the observed precipitation over the main watershed in South Korea during the historical period. An integrated selection approach based on four spatial performance assessment metrics was proposed to better estimate changes in precipitation using the simulated GCMs precipitation. Results revealed that the spatial performance over different GCMs could provide an effective means of selecting GCMs for hydrological study over the major river watersheds in South Korea. The four top-ranked GCMs are FIO-ESM-2-0, CESM2-WACCM, CESM2, and CMCC-ESM2, and they overestimated precipitation in South Korea during the historical period, with a bias of 10–25%. However, this study confirmed that a formal bias correction for these GCMs is not recommended prior to model selection, and the ranking of GCMs under the bias correction could be problematic. The proposed approach in this study can be applied to numerous GCMs, climate variables, and other regions to select representative GCMs to reduce the uncertainties in terms of the spatial patterns observed. HIGHLIGHTS The goodness-of-fit measures are proposed for the selection of climate models.; A comprehensive rating metric approach is proposed to evaluate the overall ranking of the GCMs.; Exploration of the spatial performance of different GCMs can effectively select GCMs.; A formal bias correction for these GCMs is not recommended prior to model selection, and the ranking of GCMs under the bias correction could be problematic.;